Increasing Incidence of Hypertension in Females by Nasira, Maryam, Salman, and Rehan (2019) - Mohammed, Alqahtani Ibtesam (International Journal of Innovative Research in Medical Science, 2019)
Hypertension is one of the cardio-metabolic risk factors that is associated with the increased burden of global morbidity and mortality. This disease is a silent threat to all individuals' health all over the world. Thus, early detection and management of this disease is critical.